Gweru complaints reporting and administration mobile application - Musesengwe, Tanaka C. (Midlands State University, 2019)
Service delivery to the citizens is the core business of the Gweru City Council. This means that they have to provide quality services always in order to keep the citizens secure from disease and crime. To enhance the quality of the services provided the city council the Gweru Complaints Reporting and administration mobile application is an effort to ease the process of lodging complaint by providing a highly available online system. This is an effort to make the city smart. A Smart City is one whose municipality uses which uses Information and Communication technologies to improve operational efficiency and to share information with the public. This system is there to solve the problem of not having a system for reporting problems and faults that encourages accountability for both the citizens and the city council. The manual system does not provide for effective communication between the city council and the citizens. A research on other existing complaints system was done and it proved that most complaint system are moving from having to visit the organisation to lodge complaints to online complaints management systems. The feasibility study was carried out to see if it was a viable project. It encompassed economic, technical and operational aspects. The system comprises of two environments that is the mobile application and the web administration application. The mobile application is intended for the citizens and the web application for the city council. The citizen can upload pictures and videos when lodging complaints and their GPS coordinates are captured. The web application will use geographical analysis to find the problem site and determine the best routes. There is an initiation by the town council to start using Geographical Information systems which is an important tool for service delivery. Installation and maintenance strategies are outlined which show all the considered strategies and ultimately the chosen strategy. The complaints mobile application is easy to understand and use and will make a difference in making the city smart. Smart cities